Археозоологічні матеріали Шестовицького могильника в колекціях Інституту археології - Хамайко, Н.В.; Яніш, Є.Ю. (Археологія і давня історія України, 2018)
У статті здійснюється огляд та короткий
аналіз археозоологічних матеріалів з досліджень
Шестовицького могильника, що зберігаються в Інституті археології НАН України. A long-term archaeological study at Shestovytsia necropolis
accumulated a significant collection, an important
part of which are archaeozoological materials. Most of the finds are stored at the Institute of Archaeology of
the National Academy of Sciences of Ukraine. V. I. Bibikova determined the bones from 35 Shestovytsia’s burial
mounds, excavated in the 1940s—1950s and published by D. I. Blifeld. Currently in the collection, there are osteological
remains from 28 complexes and 3 bones without the catalogue numbers, they were identified by Ye. Yu. Yanish.
The sample from this site includes 454 fragments of animal origin from 61 individuals minimum.